2017
DOI: 10.3389/fpsyg.2017.01178
|View full text |Cite
|
Sign up to set email alerts
|

Yearning to Give Back: Searching for Social Purpose in Computer Science and Engineering

Abstract: Computing is highly segregated and stratified by gender. While there is abundant scholarship investigating this problem, emerging evidence suggests that a hierarchy of value exists between the social and technical dimensions of Computer Science and Engineering (CSE) and this plays a role in the underrepresentation of women in the field. This ethnographic study of women's experiences in computing offers evidence of a systemic preference for the technical dimensions of computing over the social and a correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…With a lineage of research over twenty years showcasing multiple dimensions that decrease female participation, interest, aspiration, and success in CS at the K-12 and post-secondary levels [5,6,18,29,31,34,39], the findings presented here on the persistence of gender disparity are disconcerting, indeed. The data also suggests, though, that racial disparities are plausibly ameliorated when AP CS A was scaled in Chicago, and that there are preliminary courses that can improve success on the AP CS A exam (i.e., ECS).…”
Section: Discussionmentioning
confidence: 77%
“…With a lineage of research over twenty years showcasing multiple dimensions that decrease female participation, interest, aspiration, and success in CS at the K-12 and post-secondary levels [5,6,18,29,31,34,39], the findings presented here on the persistence of gender disparity are disconcerting, indeed. The data also suggests, though, that racial disparities are plausibly ameliorated when AP CS A was scaled in Chicago, and that there are preliminary courses that can improve success on the AP CS A exam (i.e., ECS).…”
Section: Discussionmentioning
confidence: 77%
“…Rigor in engineering is synonymous with “objectivity, math‐intensiveness, empiricism/positivism and reductionism” (Riley 2017, 254). This helps explain why, as a Liberal Arts student noted in a group interview: “Everybody thinks math is harder, or science is harder.” Rigor, in general, denotes a concern with precision, challenge, and a demanding commitment to exactness, often with differential impacts on women in technology‐based organizations who, already burdened with gender discrimination, feel the weight of these demands more acutely (Carrigan 2017).…”
Section: Majorismmentioning
confidence: 99%
“…This means that the hierarchies between social and technical fields are highly gendered, established and maintained by cultural pressures and expectations (Cech 2013b; Faulkner 2000a). Masculinity, technology, and the marriage between them (Faulkner 2000b; Riley 2017; Carrigan 2017) construct the frames by which students view their education, influence the ways they reproduce majorism according to neoliberal interests, and therefore, need deeper examination.…”
Section: Future Directionsmentioning
confidence: 99%
“…For the most part, such work focuses only on one particular subfield, irrespective of other fields. For example, according to Canney and Bielefeldt (2015), women in engineering and computing often indicate a desire to use technical knowledge to solve social problems (Canney & Bielefeldt, 2015;Carrigan, 2017;Margolis & Fisher, 2003); they also found that among the women in their study, this desire decreases over time. On the contrary, research has shown women in biology to indicate a persistent aspiration to address the human condition, which is linked to their desire to pursue careers primarily in medicine and healthcare (Hill, Corbett, & St. Rose, 2010;Sax et al, 2018;Wang, Degol, & Ye, 2015;Woodcock et al, 2013).…”
Section: Unpacking Stem Via Disciplinary Classificationsmentioning
confidence: 99%